2013
DOI: 10.1620/tjem.231.171
|View full text |Cite
|
Sign up to set email alerts
|

A Nine-Year Population-Based Cohort Study on the Risk of Multiple Sclerosis in Patients with Optic Neuritis

Abstract: Patients with optic neuritis (ON) are at an increased risk of developing multiple sclerosis (MS), an illness that may result in physical dysfunction and short life expectancy. Information on the conversion rate to MS of patients with ON is essential in determining the impact of ON on the incidence of MS. Previous Taiwanese studies on the risk of MS in patients with ON were all hospital based, thereby limiting the generalizability of the findings. We aimed to estimate the risk of MS in patients with ON using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
3
3
0
Order By: Relevance
“…This study finds elevated ON risk among young women, as has been reported previously (female-male ratio between 1.5:1 and 2.5:1) . This finding is possibly driven by strong association with MS in the UK population .…”
Section: Discussionsupporting
confidence: 88%
“…This study finds elevated ON risk among young women, as has been reported previously (female-male ratio between 1.5:1 and 2.5:1) . This finding is possibly driven by strong association with MS in the UK population .…”
Section: Discussionsupporting
confidence: 88%
“…The finding of overall low conversion rate to MS of Taiwanese patients complement the results of the earlier retrospective studies which reveals low risk of MS in Taiwan [2,5]. The variability in conversion rates (ranging between 8.3% to 65%) due to geographic, genetic and ethnic factors, and also due to differences in study design, frequency and duration of follow up, sample size and method of assessment is observed.…”
Section: Discussionsupporting
confidence: 78%
“…It may or may not be a precursor of multiple sclerosis (MS). The conversion rate from CIS to MS ranges from 30% to 82% [1,2,3,4,5]. None of the studies has prospectively analysed the conversion of CIS to MS in Taiwanese population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurologic conditions, such as optic neuritis, paresthesia, and dizziness, were similarly common prior to the diagnosis of MS, as expected, in both the US and UK. Optic neuritis is often the presenting symptom of MS, and longitudinal studies show that 34–75% of patients presenting with optic neuritis in the UK and US develop MS [ 22 , 23 ] and a relative risk > 30 for MS for Chinese individuals with optic neuritis followed for 9 years [ 24 ]. The prevalences of other symptoms such as treated depression and malaise or fatigue were also similar in the two databases.…”
Section: Discussionmentioning
confidence: 99%